Inhibiting DHN- and DOPA-melanin biosynthesis pathway increased the therapeutic value of itraconazole in Madurella mycetomatis infected Galleria mellonella. (22nd January 2022) - Lim, Wilson; Konings, Mickey; Parel, Florianne; Eadie, Kimberly; Strepis, Nikolaos; Fahal, Ahmed; Verbon, Annelies; van de Sande, Wendy W J
Abstract: Eumycetoma is a neglected tropical disease, and Madurella mycetomatis, the most common causative agent of this disease forms black grains in hosts. Melanin was discovered to be one of the constituents in grains. Melanins are hydrophobic, macromolecular pigments formed by oxidative polymerisation of phenolic or indolic compounds. M. mycetomatis was previously known to produce DHN-melanin and pyomelanin in vitro. These melanin was also discovered to decrease M. mycetomatis 's susceptibility to antifungals itraconazole and ketoconazole in vitro . These findings, however, have not been confirmed in vivo. To discover the melanin biosynthesis pathways used by M. mycetomatis in vivo and to determine if inhibiting melanin production would increase M. mycetomatis's susceptibility to itraconazole, inhibitors targeting DHN-, DOPA- and pyomelanin were used. Treatment with DHN-melanin inhibitors tricyclazole, carpropamid, fenoxanil and DOPA-melanin inhibitor glyphosate in M. mycetomatis infected Galleria mellonella larvae resulted in presence of non-melanized grains. Our finding suggested that M. mycetomatis is able to produce DOPA-melanin in vivo . Inhibiting DHN-melanin with carpropamid in combination with the antifungal itraconazole also significantly increased larvae survival. Our results suggested that combination treatment of antifungals and melanin inhibitors can be an alternative treatment strategy that can be further explored. Since the common black-grain eumycetoma causing agents uses similar melanin biosynthesis pathways, this strategy may be applied to them and other eumycetoma causative agents. Lay Summary: Melanin protects fungi from environmental stress and antifungals. We have discovered that Madurella mycetomatis produces DHN-, pyomelanin and DOPA-melanin in vivo . Inhibiting M. mycetomatis DHN-melanin biosynthesis increases therapeutic value of the antifungal itraconazole in vivo .